The The Impact of Generative Artificial Intelligence on Relationship Marketing and Brand Value": A Field Study of Employees in Battery and Tire Manufacturing Companies in Iraq: Dampak Kecerdasan Buatan Generatif terhadap Pemasaran Hubungan dan Nilai Merek": Studi Lapangan terhadap Karyawan di Perusahaan Manufaktur Baterai dan Ban di Irak - Hussein , Sajjad Khalaf (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
This study examines how generative artificial intelligence (AI) enhances brand value in automotive tire and battery manufacturing companies, with relationship marketing acting as a mediating factor. A descriptive-analytical approach was used, surveying 151 purposively selected employees from marketing, sales, customer service, and IT departments. Data were analyzed using correlation and regression techniques, with measurements showing high reliability (Cronbach’s Alpha: 0.856–0.917) and suitability for parametric analysis. Results indicate a strong positive relationship between AI and relationship marketing (r = 0.739), and regression confirms that AI significantly influences both relationship marketing (explaining 54.7% of variance) and brand value (48.5% explained variance), with relationship marketing contributing to a total mediation effect of 62.4%. The findings conclude that integrating AI into customer engagement strategies significantly boosts brand value through improved relationship marketing. This study provides strategic insights for firms aiming to leverage AI technologies to build customer trust, strengthen brand equity, and gain competitive advantage in industrial markets.